PERBAIKAN STRUKTUR TANAH PADA LAHAN SANGAT CURAM DENGAN MENGGUNAKAN TEKNIK HIDROSIDING LUMUT DAUN DAN BAHAN PEMBENAH TANAH - Busri Saleh (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2010)
[STABILITY IMPROVENT OF STEEP HILL SOIL STRUCTURE BY MEANS OF HYDROSEEDING OF MOSSES AND SOIL CONDITIONERS]. Steep hill is very sensitive to soil erosion and land slide. The objective of this study was to determine the effects of mosses (musci) and soil conditioners applied through hydroseeding technique on the development moss colony and stability of soil structure of steep hill. A randomized complete block design with three replications was used to allocate the treatment combinations of soil conditioners (no soil conditioner, water + manure, and water + manure + latex) and moss species (no moss, Andrea petrophila, and Polytricum commune).  1m x 1m plots were made on steep hill with 65% inclination and each plot was sprayed with 2 L of the soil conditioner and moss mixture (hydroseeding). Observations were made on the moss development and soil physical properties. The results showed that the moss colony increased significantly as applied with soil conditioners.  The highest colony size of moss was found on the application of water + manure + latex (200.85 m-2), followed by water + manure with (156.46 m-2), whereas no soil conditioner produced the lowest (104.91 m-2).  Hydroseeding of moss and soil conditioner had significantly improved the stability of soil structure . Combination of Polytricum commune and water + manure + latex produced the highest improvement in soil structure stability by 93.3 % as compared to the control.